Hearing Aid Fitting Method Based on Fuzzy Logic Processing - SUCHOMSKI, Piotr; KOSTEK, Bożena; CZYŻEWSKI, Andrzej (Archives of Acoustics, 2008)
One of the most important steps in a hearing aids fitting procedure is determining hearing dynamic characteristics. The hearing dynamic characteristics are typically calculated on the basis of loudness scaling test results. The problem is that the loudness scaling test results are presented on a loudness category scale, but a hearing prosthesis requires numerical parameters to be fed. A fuzzy logic method is useful for processing parameters expressed in human natural language. In this paper a fuzzy logic-based system for loudness scaling result processing is shortly presented. On the basis of the developed fuzzy system a way to shorten the loudness scaling test was found out.